The Role of Single Parents in Forming Noble Morals at the Age of 7-12 Years in the IX Tanah 600 Environment, Medan Marelan District - Erni, Erni; Lubis, Sakban (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Morality in children aged 7-12 years in Lingkungan IX Tanah 600, Medan Marelan District. Based on an interview with a single parent mother, this study shows that single parents have an important role in instilling moral values such as honesty, respect, and manners to their children. This study uses a descriptive qualitative approach, which is a type of research that aims to describe and understand in-depth the phenomenon of the role of single parents in forming morality in children aged 7-12 years. Despite facing challenges, single parents can shape their children's personalities with the support of the environment and loving parenting methods